In-Between Discipline And Control: Ari Aster's Midsommar As An Allegory For Hypercapitalist Society - Rabbi Antaridha; Widya Fhitri (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
Horror’s disruptive quality in that it continually demonstrates how the monstrous and evil circulate, invading complacent individuals, turning them into what they think as their opposites. This means that horror films possess a potential to show people that there is a possibility that the evil of the primal and primitive resides behind the veil of moral superiority and intellectual achievement of the modern world. Ari Aster’s horror film entitled Midsommar (2019) exploits the metaphorical power of the horror in revealing how the archaic is actually in the possession of the modern/“cultured”/“civilized”. The film is a reflection of the monstrosity of the systems that govern the contemporary society—a hypercapitalist society that is in-between Disciplinary Society and the Society of Control; Society of (Semi-)Control. This study mainly draws from Deleuze, Foucault, and Neo-Marxists. Data is collected by using observation method. As for data analysis methods, this study utilizes formalist technique called close reading and then apply the theoretical frameworks in an accordance with the methodological implications found in them. It is found that the narrative and visual elements of the film allegorically depict crucial aspects of a Disciplinary Society, Society of (Semi-)Control, and hypercapitalist society. The film unveils the oppressive and repressive nature of late-stage capitalism and Society of (Semi-)Control. This is shown through the customary suicide of old people because they are assumed to have past their productive years in a ritual called ättestupa; the strict division of labor; the deliberate reproduction of disable people; and the restriction to express one’s ownership of personal pain and sadness could be interpreted as elements that construct an allegory for a hypercapitalist society. Moreover, through its heroine, Dani, Midsommar also explores the process of how Disciplinary Society transforms into Society of (Semi-)Control.